How performance management is killing performance and what to do about it : rethink, redesign, reboot - Chandler, M. Tamra (Berrett-Koehler Publishers, 2016)
A step-by-step guide to creating a performance management solution tailored to your organization's needs and goals in order to meet the three objectives of great performance management: developing your people, rewarding them equitably, and driving your organization's performance.